Kontribusi Studi ‘Ulumul Qur’an Karya Ilmuwan Indonesia di Perguruan Tinggi dalam Rentang Tahun 2009-2020 - Maya, Rahendra (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Contribution of Qur’anic Studies by Indonesian Scientists in Higher Education in the Year 2009-2020 This article examines various works of Qur’anic Studies written by Indonesian scientists that are utilized and widely used as references in universities and their contributions; because so far what has been used as a reference is the work of Qur’anic Studies in Arabic or some of its translations. This research was conducted in the form of qualitative research with library research methods with data collection techniques in the form of documentation of literature of Qur’anic Studies so that the printed version can be traced physically and/or published online in the form of complete soft file to be analysed descriptively-interpretatively. From the research in general, it was concluded that in the period of 2009-2020, the works of Qur’anic Studies from scientists in this field of science in Indonesia experienced a significant and increasing number of works, with the discovery of 21 more works than previous research, and they have not been used as an object of research. These works are the real contribution of Indonesian scientists in writing the work of Qur’anic Studies. Therefore, it is hoped that these works can be a reference source in the Qur’anic Studies course and then used as a reference source in the bibliography for subsequent works, equal to the works of other scholars of the Islamic world